„Przepisanie historii” czy pogłębienie edukacji psychologicznej? Uwagi na marginesie książki Michała Bilewicza "Traumaland. Polacy w cieniu przeszłości" - Kolbuszewska, Jolanta (1973– ) (Instytut Historii PAN, 2025)
This article focuses on the book Traumaland. Polacy w cieniu przeszłości [Trau-maland. Poles in the Shadow of the Past](2024), famous in Poland for some time, authored by social psychologist Michał Bilewicz. The review’s author examined the book’s central theses, focusing primarily on rewriting and reinterpreting national history. She analysed not only the book itself but also Bilewicz’s promotional statements, interviews, and speeches. From a historical science perspective, she critically addressed his suggestions for altering the discourse surrounding recent history.
p. 243-256
Concerns book: Traumaland : Polacy w cieniu przeszłości / Michał Bilewicz. - Kraków : MANDO, 2024.
Summary in English.
Keywords: national history; historical trauma; World War II; World War, 1939-1945 - Poland; reinterpretation of national history; social psychology; history of historiography; Poland - historiography; historiography - Poland; psychological trauma - social aspect; historia - aspekt psychologiczny